TI_GERICHTE 36.2007.75 vom 4. Juni 2007 , Prescrizione di una richiesta di prestazioni all'assicuratore malattie privato. - TI Tribunale d'appello (2007)
Prescrizione di una richiesta di prestazioni all'assicuratore malattie privato.